2019
DOI: 10.1175/waf-d-18-0211.1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Tornado Events and Warnings in the Southeastern United States

Abstract: The southeastern United States has become a prime area of focus in tornado-related literature due, in part, to the abundance of tornadoes occurring in high-shear low-CAPE (HSLC) environments. Through this analysis of 4133 tornado events and 16 429 tornado warnings in the southeastern United States, we find that tornadoes in the Southeast do indeed have, on average, higher shear and lower CAPE than tornadoes elsewhere in the contiguous United States (CONUS). We also examine tornado warning skill in the form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Between 1998and 2007, Schoen and Ashley (2011 found that more than 90% of tornado deaths were associated with supercells, and also that supercells resulted in a mean of three fatalities per fatal storm, while other storm modes resulted in values closer to one fatality per fatal storm. Anderson-Frey et al (2019) also found, for 2003-17, a higher mean percentage of deadly tornadoes with an RMS storm mode versus a QLCS storm mode.…”
Section: B Storm Modementioning
confidence: 69%
See 2 more Smart Citations
“…Between 1998and 2007, Schoen and Ashley (2011 found that more than 90% of tornado deaths were associated with supercells, and also that supercells resulted in a mean of three fatalities per fatal storm, while other storm modes resulted in values closer to one fatality per fatal storm. Anderson-Frey et al (2019) also found, for 2003-17, a higher mean percentage of deadly tornadoes with an RMS storm mode versus a QLCS storm mode.…”
Section: B Storm Modementioning
confidence: 69%
“…This paper employs a NOAA Storm Prediction Center dataset of 16 232 tornado events occurring during the 15-yr period from 2003 to 2017. Smith et al (2012) described the initial creation of this dataset, and the update of the data through 2017 was discussed and these data were applied in Anderson-Frey et al (2019). This dataset filters county tornado segment data, keeping only the highest (E)F-scale value occurring within a given hour and 40 km 3 40 km area; as a result, any tornadoes occurring within the same 1 h 3 40 km 3 40 km are grouped together as a single event.…”
Section: A Tornado Event Databasementioning
confidence: 99%
See 1 more Smart Citation
“…SRH is an important parameter for characterizing the environments associated with both supercells and tornadoes, particularly for 0-1-and 0-3-km layers (Thompson et al 2003(Thompson et al , 2012Anderson-Frey et al 2016;Coffer et al 2019Coffer et al , 2020Coniglio and Parker 2020). ERA5 tends to overestimate SRH with ME of around 5 m 2 s 22 , whereas for MERRA-2 ME is close to zero, while MAE for both reanalyses is around 30 m 2 s 22 (Table 3, Fig.…”
Section: Wind Parametersmentioning
confidence: 99%
“…8). However, it can be also noted that MERRA-2 has overall better performance in sampling high-shear, low-CAPE environments (HSLC; Sherburn and Parker 2014;Anderson-Frey et al 2019;Gatzen et al 2020) than ERA5. Compared to observations, both reanalyses have more frequent situations with marginal both instability and wind shear.…”
Section: E Composite Parametersmentioning
confidence: 99%